Plan estratégico de la “Vidriería Económica” de la ciudad de Quito, para el período 2014-2018 - Freire Castro, Miryan Elizabeth (2014)
His work is focused on is the implementation of a strategic plan, it will allow the proper development of the "Economic Glass," by applying the strategies was achieved meet the objectives. Today companies support internal and external situations that affect economically and do not allow market positioning. This is where the importance of having a well-defined strategic plan for the proper performance of activities, because this document is a tool that helps management and process improvement through optimization of resources is. This work will help you make the best decisions to achieve the goals and objectives that have been proposed, seeking alternative development company. The well-defined strategies will help to solve the various problems facing the daily "Economic Glass" through the determination of operational and strategic short and medium term objectives, which socialize and be implemented during the set period.